Islam as Priority in Saudi Foreign Policy (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article discusses the backbone role of religion in shaping the domestic and foreign policy of Saudi Arabia. Saudi Arabia positions itself as the center of the Muslim world and the flagship of Islamic countries. Relations with the Muslim world are considered a priority in foreign policy, which consists of several levels of interaction in the external environment. The Kingdom pursues a proactive foreign policy both on a bilateral basis and at the level of multilateral formats and organizations.